Pemanfaatan Tumbuhan Obat Tradisional oleh Suku Mee di Distrik Kamuu, Kabupaten Dogiyai, Papua - Sipriana Dogomo; Rosye H.R. Tanjung; Suharno Suharno (Jurusan Biologi FMIPA Universitas Cenderawasih, 2020)
Plants are widely used by the community as traditional medicine in an effort to maintain health. The purpose of this study was to determine the diversity of plant species used as traditional medicines and how to use them by the Mee Tribe in Kamuu District, Dogiyai Regency, Papua. The study was conducted in December 2018-July 2019. The method used in this study was a qualitative method with observation, interview, and documentation. The research showed that are 59 species of plants from 30 families that are used as medicinal plants by the Mee Tribe community. The community uses medicinal plants by: without processing 38 species, boiling 10 species, burning 7 species, and more than one way 4 species. The plant parts used are: stem (14 species), fruits (7 species), flowers (3 species), leaves (20 species), bark (2 species), tubers (1 species), and more than one part (12 species). The most widely used part of medicinal plants is leaves (33.89 %). Key words: medicinal plant, Mee, community, Dogiyai